2017
DOI: 10.17582/journal.sja/2017/33.4.674.679
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Heritability, Genetic Advance and Correlation for Marphological Traits in Spring Wheat

Abstract: P akistan has diverse agro-ecological regions comprising both plains and mountains of Baluchistan, Punjab, Sindh, Khyber Pakhtunkhwa (KP), Azad Jammu and Kashmir and Gilgit-Baltistan. These regions include high precipitous valleys and irrigated plains. The environmental issues such as temperature fruitfulness status, soil distinctiveness and rainfall play a vital role in the varietal recital. Wheat is successfully grown in Khyber Pakhtunkhwa. It occupies 40% of the total cropped area and 60% of the area grown … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 3 publications
(3 reference statements)
4
6
0
Order By: Relevance
“…Spike length is one of the most imperative traits which accommodates a greater number of spikelets per spike (Iqbal et al, 2017). In the present study, a diverse range in spike length 13.66-10.85cm, 13.93-11.05cm, and 11.71-11.33cm was observed in M5, M6, and M7 generations respectively.…”
Section: Morphological Traits Data Of Three Mutant Generations (M5 M6 and M7)supporting
confidence: 50%
“…Spike length is one of the most imperative traits which accommodates a greater number of spikelets per spike (Iqbal et al, 2017). In the present study, a diverse range in spike length 13.66-10.85cm, 13.93-11.05cm, and 11.71-11.33cm was observed in M5, M6, and M7 generations respectively.…”
Section: Morphological Traits Data Of Three Mutant Generations (M5 M6 and M7)supporting
confidence: 50%
“…Considerable variability was observed for these traits although the expression of such traits is greatly affected by the environmental factors. Days to 50% headings is an important trait that directly or indirectly contribute to grains yield and can successfully be used as selection criteria in selection of high yielding genotypes (Iqbal et al, 2017;Singh and Chaudhary, 2006;Jolánkai et al, 2006). For flag leaf area our results were comparable with findings of Atkinson et al (2008); Dodig et al (2007) and Kenzevic et al (2007).…”
Section: Resultssupporting
confidence: 84%
“…Morphology of the agronomic traits: Analysis of variance for agronomic traits like days to 50% heading and flag leaf area and plant height showed high significant difference, while checks show non-significant differences for these traits. Highly significance differences for flag leaf area was also depicted in findings of Iqbal et al (2017). Considerable variability was observed for these traits although the expression of such traits is greatly affected by the environmental factors.…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…Under normal sowing, heritability of all the traits were more than 80% and under late sowing, heritability of only number of tillers was 75% while all other were more than 80%. High value of heritability showed that all the studied traits are valuable for breeding and can result in a significant genetic advance for late sown wheat (Iqbal et al 2017;Mwadzingeni et al 2017;Alonso et al 2018;Balkan 2018) but for the selection of traits further studies may be conducted to confirm the gene action governing these traits as Broad sense heritability estimates cannot predict the type of gene action. Alonso et al (2018) also suggested that selection of traits with higher heritability increase the genetic progress in next generations.…”
Section: Discussionmentioning
confidence: 99%